Oxygen deficit and H2S in hemorrhagic shock in rats - Van de Louw, Andry; Haouzi, Philippe (Critical Care, 2012)
Hemorrhagic shock induced O2 deficit triggers inflammation and multiple organ failure (MOF). Endogenous H2S has been proposed to be involved in MOF since plasma H2S concentration appears to increase in various types of shocks and to predict mortality. We tested the hypothesis that H2S increases during hemorrhagic shock associated with O2 deficit, and that enhancing H2S oxidation by hydroxocobalamin could reduce inflammation, O2 deficit or mortality.